STUDY ON THE ANALYSIS AND APPLICATION OF ETHNIC CULTURAL SYMBOLS IN THE COMMUNICATION OF GUIZHOU "VILLAGE SUPER LEAGUE" (Lex localis - Journal of Local Self-Government, 2025)
This study takes Guizhou’s "Village Super League" (officially named "Guizhou Rongjiang [Sanbao Dong Village] Harmonious and Beautiful Village Football Super League") in China as the research object, systematically exploring the presentation, generation, application, and communication mechanism of ethnic cultural symbols in the context of modern media communication. As a public cultural event promoted by local governments and widely participated in by the general public, the "Village Super League" has transcended the single attribute of sports competition, becoming a crucial practice for the activation of ethnic cultural resources, the consolidation of cultural identity, and social exchange. Guided by the theoretical frameworks of Semiotics, Cultural Representation Theory, and Participatory Communication Theory, this study integrates methods such as field investigation, event video and new media text analysis, and social network analysis. The findings reveal that ethnic cultural symbols in the "Village Super League" are organically integrated into the event through costumes, singing and dancing, folk customs, and cuisine. These symbols are reproduced through short videos, live broadcasts, User-Generated Content (UGC), and algorithmic recommendations, generating extensive social influence and promoting the construction of cross-regional cultural identity. The results indicate that the application of ethnic cultural symbols is not only a process of cultural representation but also a key path to enhance social cohesion and shape local cultural brands. Theoretically, this study enriches the communication perspective in ethnic cultural symbol research; practically, it provides references for grassroots public cultural construction and local cultural brand shaping.